1978
DOI: 10.1037/0022-006x.46.6.1379
|View full text |Cite
|
Sign up to set email alerts
|

Marital satisfaction and depression as predictors of physical health status.

Abstract: This study investigated the multiple correlation between physical health status and a set of marriage-related "predictor" variables. Family practice physicians provided a sample of 104 married couples. Marital satisfaction, depression, number of visits to physician, and educational level were among the set of cross-validated "predictors" of reported physical health status. The correlation between physical health status and depression was significantly greater for wives than husbands. For wives, marital satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
1

Year Published

1985
1985
2003
2003

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 13 publications
(11 reference statements)
4
23
1
Order By: Relevance
“…Weiss and Aved found that for women, poor marital satisfaction was associated with worse physical health status, whereas for husbands, marital satisfaction was related to depression and appeared to be independent of the husband's physical health status (8). In Gottman and Levenson's study mentioned above, couples with an excess of negative interactions also reported being in poorer health than couples with more positive interactions (7).…”
Section: Introductionmentioning
confidence: 91%
“…Weiss and Aved found that for women, poor marital satisfaction was associated with worse physical health status, whereas for husbands, marital satisfaction was related to depression and appeared to be independent of the husband's physical health status (8). In Gottman and Levenson's study mentioned above, couples with an excess of negative interactions also reported being in poorer health than couples with more positive interactions (7).…”
Section: Introductionmentioning
confidence: 91%
“…Marital discord and depressive symptomatology are robustly related when measured concurrently (Beach, Sandeen, & O'Leary, 1990;Heim & Snyder, 1991;Weiss & Aved, 1975;Weissman, 1987). Indeed, in the best community survey data collected to date, Weissman (1987) reported that a discordant marital relationship was a strong risk factor for unipolar depression, increasing risk of major affective disorder 25-fold for both men and women.…”
mentioning
confidence: 99%
“…Cross-sectional and retrospective studies have shown a relationship between marital decay and general psychological breakdown (Beisser & Glasser, 1968;Paykel et al, 1975), and especially between marital decay and depressive symptomatology (Colemarf & Miller, 1975;Ilfeld, 1977;Weiss & Aved, 1978;Weissman, Paykel, Siegel, & Klerman, 1971). These studies demonstrate that psychiatric patients are more likely to be in severely deteriorated marriages than other couples.…”
mentioning
confidence: 99%